Kesulitan Membaca Siswa (Studi Kasus di Sekolah Dasar) - Khusnia, Mungalimatul; Kholidin, Nor; Pravitasari, Dyah (Universitas Nurul Huda, 2022)
Reading difficulty is basically a symptom appearing in various types of behavioral manifestations, either directly or indirectly, the most basic of all learning difficulties in reading difficulty. This research used a qualitative approach and the type of this research was a case study. The data collection techniques were observation, interviews, and documentation. The data analysis technique was the interactive model of quantitative data analysis (Miles and Huberman) that was data reduction, data display, and taking conclusion. The result of this research presented that the cause of students experiencing the reading difficulty was because internal and external factors. The internal factors involved intelligence level, the lack of motivation, and the lack of interest to read. The external factors that caused students experiencing reading difficulty were family conditions and parents' economic situation. The strategy used by teacher to help students undergoing reading difficulty was cooperation with parents, giving learning guidance and always giving motivation. The teacher obstacle factors to help students experience reading difficulty was social environment factors, environment factor in school and the lack of the student awareness experiencing reading difficulty. The supporting teacher factors to help students undergoing reading difficulty were using learning media, family factors, and student interest of reading.